Supplementation of ammonium bicarbonates for the treatment of fruit cordial wastewater by anaerobic digestion process - Redzwan, G.; Banks, C.J. (Elsevier, 2010)
Lack of nitrogenous substrate and buffering capacity have been identified as causing failure in previous work on the treatment of fruit cordial wastewater using anaerobic continuous stirred tank reactors. In this study, ammonium bicarbonate was proposed to be used as the substrate for nitrogenous and buffering resources. In order to determine the toxicity effect of the ammonium salts on the anaerobic system, a series of concentration from 0 to 40 mg L-1 was tested. Biogas production was used as the indicator for NH4þ toxicity. The results showed no indication that methanogen was affected by the additional ammonium salt within the dosing regime. Application of the specific mathematical function (G ¼ Gm k/t) to describe the kinetic of biogas production, suggested that the optimal concentration of ammonium bicarbonate that can be used is 10 mg L-1. This study also shows that the dosage regime up to 40 mg L-1 can be used to supplement the lack of nitrogenous and buffering capacity for the anaerobic digestion process of the fruit cordial wastewater using CSTR.